Congenital Rubella Syndrome in Fiji, 1995–2010. (3rd February 2013) - Singh, Sheetalpreet; Bingwor, Frances; Tayler-Smith, Katherine; Manzi, Marcel; Marks, Guy B.
Abstract : Setting . A nationwide study in Fiji. Objective . To describe the incidence of congenital rubella syndrome (CRS) and its relationship to the incidence of notified cases of rubella in Fiji from 1995 to 2010. Design . Descriptive, retrospective review of all recorded congenital abnormalities associated with live births in Fiji over 16 years. Results . There were 294 infants who met the criteria for CRS. Of these, 95% were classified as "suspected" cases, 5% were "clinically confirmed, " and none were "laboratory confirmed cases". There was a significant linear increase over the study period in the incidence of CRS (odds ratio 1.045 per year, 95% CI 1.019 to 1.071, P ≤ 0.001 ). There was no significant association between the incidence of CRS and the reported incidence of rubella (P = 0.3 ). Conclusion . There is a rising trend in reports of suspected CRS cases in Fiji. This highlights the need to strengthen surveillance for CRS through improvements in clinical and laboratory diagnosis to confirm or exclude suspected cases. It is also important to ensure high coverage of rubella vaccination in Fiji.